MRI‐Compatible and Conformal Electrocorticography Grids for Translational Research. Issue 9 (8th March 2021) - Fallegger, Florian; Schiavone, Giuseppe; Pirondini, Elvira; Wagner, Fabien B.; Vachicouras, Nicolas; Serex, Ludovic; Zegarek, Gregory; May, Adrien; Constanthin, Paul; Palma, Marie; Khoshnevis, Mehrdad; Van Roost, Dirk; et al.
Abstract: Intraoperative electrocorticography (ECoG) captures neural information from the surface of the cerebral cortex during surgeries such as resections for intractable epilepsy and tumors. Current clinical ECoG grids come in evenly spaced, millimeter‐sized electrodes embedded in silicone rubber. Their mechanical rigidity and fixed electrode spatial resolution are common shortcomings reported by the surgical teams. Here, advances in soft neurotechnology are leveraged to manufacture conformable subdural, thin‐film ECoG grids, and evaluate their suitability for translational research. Soft grids with 0.2 to 10 mm electrode pitch and diameter are embedded in 150 µm silicone membranes. The soft grids are compatible with surgical handling and can be folded to safely interface hidden cerebral surface such as the Sylvian fold in human cadaveric models. It is found that the thin‐film conductor grids do not generate diagnostic‐impeding imaging artefacts (<1 mm) nor adverse local heating within a standard 3T clinical magnetic resonance imaging scanner. Next, the ability of the soft grids to record subdural neural activity in minipigs acutely and two weeks postimplantation is validated. Taken together, these results suggest a promising future alternative to current stiff electrodes and may enable the future adoption of soft ECoG grids in translational research and ultimately in clinical settings. Abstract : Current clinical electrocorticography (ECoGs) grids are made from stiff materials and only offer sparse brain sampling during epilepsy or tumor surgeries. Here conformable ECoG grids made from silicone membranes permit easy implantation in hidden anatomical locations in cadaveric specimen and imaging compatibility with 3T magnetic resonance imaging. In vivo in a minipig model the conformable ECoG grids show high‐resolution brain recordings.